Efficacy of biopesticides on spotted wing drosophila, Drosophila suzukii Matsumura in fall red raspberries. (24th October 2017) - Fanning, P. D.; Grieshop, M. J.; Isaacs, R.
Abstract: Drosophila suzukii Matsumura is a significant pest of soft‐skinned fruit. Larvae of D. suzukii develop within the fruit making it unmarketable as fresh berries and increasing the risk of rejection by processors. We evaluated selected biopesticides for control of D. suzukii in fall red raspberries, Rubus idaeus L. The trial results highlight a small number of biopesticides with the potential to reduce infestation of Drosophila larvae in raspberries. In addition to the standard biopesticide spinosad, we found that sabadilla alkaloids and Chromobacterium subtsugae both reduced the number of Drosophila larvae in raspberry fruit. Treatments that included corn syrup as a feeding stimulant showed no significant difference in their infestation levels compared to treatments without the syrup. In the final week of the 5‐week trial, treatments with rotations of either spinosad/ C. subtsugae or spinosad/sabadilla alkaloids had a 67% and 57% reduction in infestation when compared to untreated raspberries. Treatments of spinosad alone on a 7 day rotation and C. subtsugae alone on a 3–5 day rotation both had a 62% and 61% reduction in larval infestation when compared to untreated raspberries. Third instar larvae, the largest and most damaging, were significantly reduced in plots treated with spinosad only, a rotation of spinosad/sabadilla alkaloids and the rotation of spinosad/ C. subtsugae with corn syrup added when compared to untreated plots. This suggests that either of these biopesticides could be used as effective rotation partners along with spinosad for control of D. suzukii . Our results highlight that biopesticides can provide significant reduction in this devastating pest when used alone or in combination, providing options to support resistance management.